Identifying Risk Factors for Speech Delay in Children Aged 2-4 Years in Surabaya, Indonesia - Mahira Khansa Aishaneeqa; Irwanto; Dwi Aprilawati; Noor Idha Handajani (Journal of Community Medicine and Public Health Research, 2026)
Speech delay presents a complex problem with a diverse range of contributing factors. Early identification of risk factors for speech delay in children is crucial to allow for immediate treatment and minimize adverse outcomes. This research identifies several risk factors for speech delay in children aged 2-4 years in Surabaya. Using the Chi-square test and logistic regression analysis, secondary data were collected through medical records at Dr. Soetomo General Academic Hospital, Surabaya. The subjects consisted of 223 children aged 2-4 years with speech delay and 177 children aged 2-4 years without speech delay. Multivariate analysis revealed that gender (OR 1,726; 95%CI 1,069 to 2,788; p=0,026), excessive screen time (more than 6 hours daily) (OR 8,850; 95%CI 1,493 to 52,458; p=0,016), and history of congenital abnormalities (OR 0,256; 95%CI 0,122 to 0,537; p<0,001) were significantly associated with an increased risk of speech delay in children. On the other hand, factors such as father's and mother's occupation, parental education, family history of developmental delay, maternal health during pregnancy, gestational age, childbirth delivery method, number of siblings, birth order, birth conditions, birth weight, nutritional status, history of icterus, hearing loss, and oral motor disorders were not proven as risk factors for speech delay in children. In conclusion, gender, excessive screen time (more than six hours daily), and a history of congenital abnormalities are risk factors for speech delay in children